Forest Recreation and Landscape Protection - Pintilii, Radu-Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nowadays, Forestry has become an important field for the Environmental and Earth sciences due to its importance in global systems. While forest recreation focuses on forests as the main destination for public recreational activities, landscape protection refers to the conservation and restoration of natural beauty. Urban and peri-urban forests have become a place for the recreational activities of people living in big cities. They provide benefits to the quality of life. Landscape protection is also important, not only for scientific and ecological reasons but also for social and cultural ones. This reprint presents different contributions by the authors dealing with recent scientific research on forestry, recreational activities, landscape management, ecosystem services, etc., in different areas of the world.